Polynias im antarktischen Meereis im Kieler Klima Modell - Golde, Sandra (2018)
Polynya are defined as a special phenomenon in the Southern Ocean. It describes an open area of sea water that is surrounded by sea ice. The first occurance of a polynya was detected by satellite in 1974. Polynya can be explained by deep convection in the ocean. In the water column, destabilization occurs due to cooling of the upper ocean layer causing a combination of sinking colder water masses and rising warmer masses. Polynya research is an important aspect of climate change. In this thesis ten global warming simulations are compared to each other as well as to a control run with data based on the Kiel Climate Model. The simulations are subject to a time scale of 200 model years. The CO2 concentration increases by 1% year until it is four times the greenhouse gas value. A control run with constant C02 is run for 3700 model years. The relevant parameters for the genesis of polynya are examined before explaining and comparing effects of increasing greenhouse gas concentration. Area and time of interest are eastwards of the Weddell Sea and the month September. The relevant parameters for polynya occurence are mixed layer depth, sea ice concentration, temperature and salinity. The global warming simulations show a correlation of r=-0.78 between decreasing mixed layer depth and reduction of sea ice concentration. For all simualtions a rise in CO2 concentration can be detected. The reaction starts after the first 50 model years and is strong enough to shut down the deep convection, resulting in a complete absence of polynya. Similarly, an increase in temperature can be seen for the entire water column. The salinity stays constant with rising CO2, except for during active convection.